2018
DOI: 10.18805/lr-389
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium sp.CCNWYC119: a single strain highly effective as biofertilizer for three different peas (Pigeon pea, Sweet pea and Chick pea)

Abstract: Rhizobium spp. was isolated from root nodules of Pigeon pea (Cajanus cajan L.), Sweet pea (Lathyrus sativus L.), Chick pea (Cicer arietinum L.). The isolates ware rod shaped, aerobic, gram negative, motile and non-spore forming. Isolates were positive to Catalase, Citrate utilization, Urea hydrolysis, Congored, Nitrification, Oxidase, Triple sugar iron and MacConkey agar test. The isolates can ferment all nine sugars. Then, the isolates identified as Rhizobium spp. depending on above results were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…(2005) reported that plant height, number of branches, plant fresh and dry weights, umbels number and fruits yield increased with nitrogen and bio-fertilizer treatment in Anethum graveolens, with the high dose of nitrogen producing the highest values. Nushair et al, (2018) also reported in Pigeon pea, Sweet pea and Chick pea that bio fertilizer application significantly increased plant height pod and seed weight. Hassan et al, (2012) stated that biofertilizer treatments enhanced plant height, branch number/ plant and plant dry weight.…”
Section: Description Of Experimental Areamentioning
confidence: 76%
“…(2005) reported that plant height, number of branches, plant fresh and dry weights, umbels number and fruits yield increased with nitrogen and bio-fertilizer treatment in Anethum graveolens, with the high dose of nitrogen producing the highest values. Nushair et al, (2018) also reported in Pigeon pea, Sweet pea and Chick pea that bio fertilizer application significantly increased plant height pod and seed weight. Hassan et al, (2012) stated that biofertilizer treatments enhanced plant height, branch number/ plant and plant dry weight.…”
Section: Description Of Experimental Areamentioning
confidence: 76%
“…In other report, Rhizobium spp. was isolated from root nodules of pigeon pea (Nushair et al, 2018). Previous reports on the toxinogenic potential of these fungi involved peanut cakes (S. Adjou, 2012), as well as peanut seeds gathered from Benin (Boli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is possibility of bacteria potential for bioremediation of salt from plant rhizosphere. Hence this study was undertaken for the isolation and molecular characterization of the halophilic bacteria from salt affected soils (Nushair et al, 2018). Furthermore, the soil bacteria play a very vital role in biogeochemical cycles of require nutrients resulting in better crop yield.…”
Section: Introductionmentioning
confidence: 99%